Long-term peatland condition assessment via surface motion monitoring using the ISBAS DInSAR technique - Alshammari, Lubna (2019)
Satellite Earth Observation (EO) is often used as a cost-effective method to report on the condition of remote and inaccessible peatland areas. Current EO techniques are primarily limited to reporting on the vegetation classes and properties of the immediate peat surface using optical data, which can be used to infer peatland condition. Another useful indicator of peatland condition is that of surface motion, which has the potential to report on mass accumulation and loss of peat. InSAR techniques can provide this using data from space. However, the most common InSAR techniques for information extraction, such as persistent scatterers interferometry (PSI), have seen limited application over peat as they are primarily tuned to work in areas of high coherence (i.e., on hard, non-vegetated surfaces only). A new InSAR technique, called the Intermittent Small Baseline Subset (ISBAS) method, has been recently developed to provide measurements over vegetated areas from SAR data acquired by satellite sensors, providing the opportunity to apply InSAR data to peatland studies effectively for the first time. This research examines the feasibility of the ISBAS technique applied to only C-band SAR data for monitoring long-term surface motion over two peatland areas with different environments. The first peatland area is the Flow Country in the North east of Scotland which is the largest expanse of blanket bog in Europe (open peatland area) and the second peatland area is known as Zennare Basin in the south of the Venice Lagoon, Italy, which is characterized by the presence of the marsh zone covered with peat (farmed peatland area). The assessment of long-term deformation in the Flow Country is made by analysing two sets of SAR data (ERS covering the period 1992-2000 and Sentinel-1 for the period 2015-2016). For Zennare Basin three sets of SAR data have been used in the analysis (ERS SAR data 1992-2001, ENVISAT 2003-2008, and Sentinel-1 2015-2018). The results revealed that the ISBAS DInSAR technique over open peatland areas could offer extensive support for peatland surveying which would reduce the long-term monitoring cost by assessing the relative magnitude and spatial pattern of the deformed areas that are caused by, for example, drainage, afforestation or erosion which in turn provides a key information for guiding the future management. Over farm peatland areas where the coherence is highly variable, the results also revealed a real potential of using the ISBAS technique to provide a surface motion for Venice Lagoon, where the agricultural land class (unfavourable for InSAR) is the dominant class in this area. However, the limited of both ISBAS coverage and ground data on the extent of the Zennare Basin hindered the true assessment of ISBAS accuracy. In addition to the assessment of long-term deformation using the ISBAS technique, a novel analysis of the ISBAS DInSAR time-series was found linking between the characteristics of surface motion derived by InSAR and peat condition using Sentinel-1 ISBAS time-series over the Flow Country through the application of Singular Spectrum Analysis (SSA) and Multi-channel Singular Spectrum Analysis (MSSA). This research suggests that the ISBAS DInSAR technique is feasible for long-term peatland monitoring, particularly over open peatland areas, can provide new insight into peatland surface dynamic changes and helps to understand the seasonal kinematic behaviour of peatland from local to regional scales.